2004
DOI: 10.1016/j.ejvs.2004.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of the Intestinal Viability Using Oxygenated Perfluorocarbon in an Experimental Model of Acute Intestinal Ischemia

Abstract: These results suggest that intestinal viability could be prolonged after acute ischemia using oxygenated perfluorocarbons and this could be a promising pretreatment modality for a variety of mesenteric ischemic forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 16 publications
1
16
0
1
Order By: Relevance
“…Similar to our findings, other authors observed severe intestinal damages, using a light microscope, after at least 210 min of SMA ligation in rabbits [24,25]. These authors reported the presence of mucosal or transmural infarction, congestion, and mucosal hemorrhage.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to our findings, other authors observed severe intestinal damages, using a light microscope, after at least 210 min of SMA ligation in rabbits [24,25]. These authors reported the presence of mucosal or transmural infarction, congestion, and mucosal hemorrhage.…”
Section: Discussionsupporting
confidence: 93%
“…[6][7][8][9] A study reported by O'Donnell et al and also our previous histologic experimental study showed that oxygenated PFCs could preserve the intestinal viability during acute intestinal ischemia. 8,18 Despite the fact that acidosis and cardiopulmonary complications are the leading cause of death in cases of acute intestinal ischemia, no data concerning the effects of PFC-O 2 in the acid-base and cardiorespiratory parameters have been reported until now. From this point of view, in cases of a compromised intestinal blood fl ow, the attempt to reduce the metabolic response and the subsequent complications acquire obvious value, and the defi nition of this hypothesis was the purpose of this study.…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports have shown that the PFCs shared some anti-infl ammatory properties, as well as their ability to carry respiratory gases. 18,19 To establish that the possible positive effect of PFCs is dependent on the O 2 delivery capability, our protocol included a PFC group (of nonoxygenated fl uorocarbon) in addition to the two main groups (Control and PFC-O 2 ). In addition, the groups were separated into three subgroups of arterial, venous, and arteriovenous ischemia in an attempt to simulate the experimental ischemia with different clinical scenarios and to evaluate the PFC-O 2 effects in various degrees of intestinal ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these agents might reduce injury after reperfusion by enhancing delivery of oxygen to areas of impaired perfusion. Recent studies with PFC agents have shown beneficial effects in reduction of ischaemia/reperfusion injury in the intestine [2][3][4] as well as in oxygenation and reduction of ischaemic damage in an acute subdural haematoma model in rats [5]. Additionally, the application of PFC agents leads to an improvement of myocardial functional recovery after cold ischaemia and reperfusion [6].…”
Section: Introductionmentioning
confidence: 96%